Seed fungal endophytes as biostimulants and biocontrol agents to improve seed performance - Rétif, Félix; Kunz, Caroline; Calabro, Kevin; Duval, Clémence; Prado, Soizic; Bailly, Christophe; Baudouin, Emmanuel (Frontiers in Plant Science, 2023)
Seed germination is a major determinant of plant development and final yield establishment but strongly reliant on the plant's abiotic and biotic environment. In the context of global climate change, classical approaches to improve seed germination under challenging environments through selection and use of synthetic pesticides reached their limits. A currently underexplored way is to exploit the beneficial impact of the microorganisms associated with plants. Among plant microbiota, endophytes, which are micro-organisms living inside host plant tissues without causing any visible symptoms, are promising candidates for improving plant fitness. They possibly establish a mutualistic relationship with their host, leading to enhanced plant yield and improved tolerance to abiotic threats and pathogen attacks. The current view is that such beneficial association relies on chemical mediations using the large variety of molecules produced by endophytes. In contrast to leaf and root endophytes, seedborne fungal endophytes have been poorly studied although they constitute the early-life plant microbiota. Moreover, seed-borne fungal microbiota and its metabolites appear as a pertinent lever for seed quality improvement. This review summarizes the recent advances in the identification of seed fungal endophytes and metabolites and their benefits for seed biology, especially under stress. It also addresses the mechanisms underlying fungal effects on seed physiology and their potential use to improve crop seed performance.